Effect of Fibula Shortening on Medial Clear Space and Lateral Translation of the Talus: An Anatomical Cadaveric Study - Lyndon W. Mason FRCS (Tr&Orth); Niamh L. Heeran BSc (Hons); Grace Airey MBChB, MRes (Dist.); Rajkumar Gangadharan D.Orth, FRCSEd (T&O); Abdul-Rahman Gomaa BMBS MRCS PGCert PGCAPP FHEA; Alistair P. Bond PhD; Lucy Roper BSc (Foot & Ankle Orthopaedics, 2023)
Category: Ankle; Trauma Introduction/Purpose: Fibular shortening with an medial and syndesmotic ligament instability causes lateral translation of the talus. We hypothesise that the interaction of the anterior inferior tibiofibular ligament (AITFL) tubercle of the fibular with the anterior tibial incisura would precipitate lateral translation due to the size differential. Methods: Twelve cadaveric ankle specimens were dissected, removing all soft tissue except for ligaments. They were fixed onto a bespoke jig allowing tibial fixation and free movement of the talus and fibula. The fibula was progressively shortened in 5mm increments until complete ankle dislocation, measuring the medial clear space with each increment. Results: The larger AITFL tubercle interaction with the smaller tibial incisura caused a significant increase in lateral translation of the talus. This occurred in most ankles between 5-10mm of fibular shortening. The medial clear space widened following 5mm of shortening in 5 specimens (mean: 2.07, s.d: 2.53). All 12 specimens experienced widening by 10mm fibular shortening (Mean: 7.21mm, s.d: 2.21) and reached complete dislocation by 35mm fibular shortening. Conclusion: This study shows, that with fibular shortening, the interaction between the distal fibular AITFL tubercle and the anterior tibial incisura precipitates a lateral translation of the talus in an ankle fracture model where the medial and syndesmotic ligaments have been transected and the lateral ligaments remain intact. The interaction occurred between 5 and 10mm of fibular shortening. Beyond this point there was a near linear correlation between fibular shortening and medial clear space widening